La comprensión de lectura en textos de Ciencias Naturales - Santelices, L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
There are many linguistic factors and pre -scientific notions related to the process of reading comprehension of written materials used in science teaching. This paper shows these factors and proposes some strategies for increasing the reading comprehension of texts related to science teaching.